Vibrotactile Feedback Improves Manual Control of Tilt After Spaceflight - Clément, Gilles; Reschke, Millard F.; Wood, Scott J. (Frontiers in Physiology, 2018)
The objectives of this study were to quantify decrements in controlling tilt on astronauts immediately after short-duration spaceflight, and to evaluate vibrotactile feedback of tilt as a potential countermeasure. Eleven subjects were rotated on a variable radius centrifuge (216 º/s, < 20 cm radius) in a darkened room to elicit tilt disturbance in roll (≤ ± 15º). Nine of these subjects performed a nulling task in the pitch plane (≤ ± 7.5º). Small tactors placed around the torso vibrated at 250 Hz to provide tactile feedback when the body tilt exceeded predetermined levels. The subjects performed closed-loop nulling tasks during random tilt steps with and without this vibrotactile feedback of tilt. There was a significant effect of spaceflight on the performance of the nulling tasks based on root mean square error. Performance returned to baseline levels 1-2 days after landing. Vibrotactile feedback significantly improved performance of nulling tilt during all test sessions. Nulling performance in roll was significantly correlated with performance in pitch. These results indicate that adaptive changes in astronauts’ vestibular processing during spaceflight impair their ability to manually control tilt following transitions between gravitational environments. A simple vibrotactile prosthesis improves their ability to null-out tilt within a limited range of motion disturbances.